Flood Estimation Studies Using Hydrologic Modelling System (HEC-HMS) for Batu Pahat River Malaysia - Mohammed, A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Discharge is an important parameter that required in predicting flood events, especially those with great magnitudes. The outcomes of these predictions form an important part of the understanding and control risks of flooding knowledge for the authorities, planners and the general public. The hydrological data could be used to analyze the river system's reaction to deep rainfall and to draw up flood hydrographs with fair precision using the required rainfall-runoff model from the details of the rainfall. The aim of this study to understand the rainfall and water level trend for the last 11 years which was used to estimate the flow discharge derived from rainfall data for Batu Pahat, Johor. The data of rainfall and water level was collected from DID Malaysia for two different stations in Batu Pahat, which represent the rainfall and water level data for the last 10 years. Mann Kendall method was utilized to analyses the trend of these hydrological data. While the HEC-HMS software was used to estimate the flow discharge data that applied the suitable analyses method. Mann Kendall test shows the Kendall's tau value was-0.233 and-0.437 for rainfall and water level respectively. The indicated a decreasing trend for both parameters but the trend is no significant. This might be due to the missing data within these 10 years. By referring to the discharge result, it shows that the value of runoff is increase with the increasing of rainfall where the maximum value of discharge is about 960.6 cfs. Thus, based on this value, it could give an insight to the local authority to plan their strategy to accommodate this discharge within the river reach to minimize the flood event. Â© 2021 IEEE.